Epidemiology Of Animal Bite Cases Attending Municipal Tertiary Care Centers in Surat City: A Cross-Sectional Study - Umrigar, Pradeep; Parmar, Gaurang B; Patel, Prakash B; Bansal, R K (National Journal of Community Medicine, 2013)
Context: Animal bite, especially dog bite is an important public health problem in urban India. Socio-cultural practices and myths consider as major problem for post-exposure prophylaxis of animal bites. Objectives: To study the epidemiological characteristics and determinants of post-exposure prophylaxis of animal bite victims. Methodology: It was a cross-sectional study conducted among new cases of animal bites registered at Tertiary Care Centres of Surat city. Results: Out of total 382 cases of animal bites majority (58%) belongs to 15-45 years of age-group and 83 % were male. Stray dogs were involved in 94% animal bite cases. Majority (81%) of bites were unprovoked. Category II bites were seen in 204(54 %) of cases. In 81.4% cases lower extremities were affected. Only two hundred ninety two cases had attended the ARV clinic within 24 hours of bite. Only 75 % of cases had done the wound washing. Conclusion: Wound washing immediate after bite form the prime step of management of any animal bite which was absent in majority of cases.